1996
DOI: 10.1111/j.1365-2044.1996.tb15045.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas leakage and the laryngeal mask airway: A comparison with the tracheal tube and facemask during spontaneous ventilation using a circle breathing system

Abstract: SummaryThe ability of'the laryngeal mask airway, tracheal tube und facemask to provide a leak free seal in a clinical setting was assessed by measuring the minimal fresh gas flows needed in a closed circle system during spontaneous oentilation on 60 subjects. The ,fresh gas.flow was reduced until no spillage occurred,from the pop-of valve. This,fresh gas flow was taken to represent the sum of gas uptuke by the subject and gas leakage from the circuit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The safety and efficiency of the laryngeal mask airway have already been demonstrated in large clinical studies [13]. Although the laryngeal mask airway is known to form an airtight seal in patients during spontaneous ventilation [5], which allows reduction of the fresh gas flow to 0.5 L min −1 , prospective studies to evaluate the feasibility of fresh gas flow reduction during controlled mechanical ventilation of the lungs with the use of the laryngeal mask airway have not been performed. This is of particular interest as leakage may occur due to increased inspiratory pressures during positive‐pressure ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The safety and efficiency of the laryngeal mask airway have already been demonstrated in large clinical studies [13]. Although the laryngeal mask airway is known to form an airtight seal in patients during spontaneous ventilation [5], which allows reduction of the fresh gas flow to 0.5 L min −1 , prospective studies to evaluate the feasibility of fresh gas flow reduction during controlled mechanical ventilation of the lungs with the use of the laryngeal mask airway have not been performed. This is of particular interest as leakage may occur due to increased inspiratory pressures during positive‐pressure ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…The endotracheal tube has been shown to form an airtight seal between the anaesthesia circle system and the patient’s airway, and allows routine reduction of fresh gas flow down to 0.5 L min −1 . Although clinical studies assessed the possibility of fresh gas flow reduction when using laryngeal mask airway in spontaneously breathing patients [5], it has not been shown that the laryngeal mask airway permits low‐ or minimal‐flow anaesthetic methods during controlled ventilation. This study shows that the laryngeal mask airway can be used during controlled ventilation using a fresh gas flow of 0.5 L min −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, training in mask ventilation is essential for all residents. Previous studies have reported operator difficulty in attaining and holding a proper air seal [13][14][15]. Langeron et al and Clayton et al each reported that gas leakage was an important issue during difficult mask ventilation [4,16].…”
Section: Discussionmentioning
confidence: 98%
“…5 - 7 Although the LMA does not provide a watertight seal, it has been used largely during positive pressure ventilation in adults and children. 8 , 9 Some studies support the concept of safety of using LMA during low-flow anesthesia.…”
Section: Introductionmentioning
confidence: 99%